Meaning of pathogens and bacterial udabreny in agriculture (Eurasian Journal of Ecology, 2016)
The article presents data on agricultural pathogens and bacterial udrbrenii and their influence on soil fertility, as well as the value of the soil microorganism Azotobacter chroococcum.
Keywords: insecticide; pathogen; microorganism; soil; nitrogen fixers; nitrogen.